Decolonizing the histories of Helen Hunt Jackson and Gertrude Simmons Bonnin - Bilek, Barbara R. (My University, 2013)
What is decolonization and how does it work? The concept of decolonization surfaced during "the global Indigenous activism in the 1970s." Although the idea is not new, it has been given little attention by mainstream historians. A discussion of the meaning of decolonization begins with an understanding that colonization means to settle in a colony or colonies. For example, England and Spain began establishing colonies on the lands of the Indigenous Nations of the Americas in the 16th and 17th centuries. Thus, the United States began as a loosely united group of colonies making decolonization a logical consequence. As such, decolonization means to remove or mitigate the consequences of colonization. According to Susan A. Miller (Seminole), "decolonization is a process designed to shed and recover from the ill effects of colonization." In this thesis, I utilize case studies of two women to demonstrate how decolonizing history using an Indigenous lens can construct a more comprehensive history and produce a distinct narrative from a Native American perspective. I argue using this methodology recasts the activism of Helen Hunt Jackson and Gertrude Simmons Bonnin (Yankton Nakota) as the progenitor to modern Native American rights movements. The political activism of Jackson and Bonnin resides within literary journals shadowed by analyses of their fiction and poetry. Utilizing a different perspective revealed the stories of two women whose work made a significant impact on relations between the United States government and Native American nations that was generally less celebrated among historians. The object of this research project is to use an Indigenous perspective to decolonize and reclaim the histories of Helen Hunt Jackson and Gertrude Simmons Bonnin (Yankton Nakota) and their activism for Native American rights. The historical importance of the reform work of both women went unnoticed for a few decades, but the activism of the 1960s resurrected their legacy. Preliminary research indicated scholars focused primarily on the literary achievements of these Victorian Age women not their efforts to change the assimilation policies of the U.S. government. American historians infrequently accept Helen Jackson as a historian even though the production of her book A Century of Dishonor (1881) required hours of work analyzing primary source documents such as survey maps and treaties. Some Native American scholars put Jackson in the company of people called "do-gooders" or those people who supported the practice of assimilation as the best outcome for Native American tribes. In recent decades, scholars such as P. Jane Hafen (Taos Pueblo) began producing work that focused on the political importance of Bonnin's activism. Robert Warrior (Osage) labeled her as pro-assimilation because she worked for the Society of American Indians (SAI) whose constituency was comprised of Native American leaders that believed assimilation was the best way for Native Americans to articulate with the dominant culture. However, further analysis found that Gertrude left the SAI because she did not agree with her peers. This project produced a manuscript that provides an example of how to apply the principles of Indigenous discourse, as set forth by Susan Miller specifically regarding decolonization. This researcher's perspective saw Jackson and Bonnin's activism as the progenitor of modern day Native American rights movements. Jackson produced the first investigative effort to catalogue the broken treaty provisions and land misappropriations inflicted on Native American tribes by the U.S. government. Her enduring non-literary legacy was the work she did as an Indian agent for the Mission Indians of California where she worked to ensure the government treated the tribes equitably. Among Gertrude Bonnin's many accomplishments, her last and most significant was the creation of the National Council of American Indians that she co-founded with her husband in 1926. This organization preceded the modern day National Congress of American Indians. Thus, the result of this project is a decolonized narrative focused on the reform work of Helen Hunt Jackson and Gertrude Simmons Bonnin. Decolonizing the history of two very different women with synchronistic goals may encourage other historians whether Native American, western, or American to present alternative perspectives in the histories they write.
Keywords: Jackson, Helen Hunt; Bonnin, Gertrude Simmons; Decolonization; Indians of North America; Indigenous peoples